2014
DOI: 10.1017/s175173111400007x
|View full text |Cite
|
Sign up to set email alerts
|

Spread of hatch and delayed feed access affect post hatch performance of female broiler chicks up to day 5

Abstract: It is not rare that newly hatched chicks remain without feed for about 24 to 48 h before they are placed on farms due to a series of logistic operations. Furthermore, the spread in hatching time can also mount up to 30 to 48 h for late v. early hatchers. In other words, the practice is a complex combination of spread of hatch and delayed feed access. The present study was aimed to investigate the combined effects of hatching time with a delay in feed access of 48 h, starting from their hatch-time (biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
0
39
2
Order By: Relevance
“…Two main differences in experimental setup may explain the difference between the results of Peebles et al (2004) and this study: first, Peebles and colleagues could perform temperature measurements at the hatchery, whereas our measurements started later, and second, their measurements were performed under highly varying external temperatures that may have increased differences in body temperature, whereas ours were performed under more consistent conditions. Although we did not find any body temperature differences between slow-and fast-growing animals, recent studies have shown that different lengths of time between hatching and first access to feed may affect the relationship between body temperature and growth, with low levels of T 3 being associated with increased early growth when chicks start feeding soon after hatching but not in initially fasted chicks (Wang et al, 2014(Wang et al, , 2016. This suggests a potential confounder that we could not correct for, as all chicks used in this study came from commercial hatcheries that do not record individual hatching times.…”
Section: Discussioncontrasting
confidence: 91%
“…Two main differences in experimental setup may explain the difference between the results of Peebles et al (2004) and this study: first, Peebles and colleagues could perform temperature measurements at the hatchery, whereas our measurements started later, and second, their measurements were performed under highly varying external temperatures that may have increased differences in body temperature, whereas ours were performed under more consistent conditions. Although we did not find any body temperature differences between slow-and fast-growing animals, recent studies have shown that different lengths of time between hatching and first access to feed may affect the relationship between body temperature and growth, with low levels of T 3 being associated with increased early growth when chicks start feeding soon after hatching but not in initially fasted chicks (Wang et al, 2014(Wang et al, , 2016. This suggests a potential confounder that we could not correct for, as all chicks used in this study came from commercial hatcheries that do not record individual hatching times.…”
Section: Discussioncontrasting
confidence: 91%
“…Supplementation of Fadrozole into chicken eggs increased the number of hatched chicks around the mode and afterwards increased the number of late hatchers. The spread of hatching time can be escalated up to 48 hours for late versus early hatchers [23]. Therefore, practically, chicks are deprived from water and feed for up to 72 hours post-hatching [69].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, practically, chicks are deprived from water and feed for up to 72 hours post-hatching [69]. On the other hand, early hatchers suffer more from being fasted compared to the late hatchers [23], have slower growth rate and immune system activity [69][71], and comprised the majority of low quality chickens [70]. Moreover, the compulsory holdup feed access is a main aggravating factor for long storage duration of hatched chicks [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have looked into the underlying physiological differences between early, midterm, and late hatched chickens within the hatch-window, by determining blood metabolites, such as glucose, lactate, uric acid, as well as thyroid hormones triiodothyronine (T3) and thyroxine (T4) (Van de Ven et al, 2011;Van de Ven et al, 2013;Wang et al, 2014b). None of these studies looked into potential effects on breast meat yield, except for Wang et al (2014), who found no effect of hatch moment nor feed access on the proportional breast muscle weight at biological age d 2 and 5.…”
Section: Intestinal Developmentmentioning
confidence: 99%